THE INFLUENCE OF THE USE OF ICT (INFORMATION AND COMMUNICATION TECHNOLOGY) ON STUDENT LEARNING OUTCOMES IN CLASS IV SCHOOL MATERIALS AT STATE 3 SIGLI PRIMARY SCHOOL - Asyikin, Farah; Mislinawati, Mislinawati; Yamin, M. (Elementary Education Research, 2024)
This research aims to determine whether there is an influence of the use of ICT (Information and Communication Technology) on student learning outcomes in grade IV fraction material at SD Negeri 3 Sigli. The approach in this research uses a quantitative approach with the True-Experimental Design type. And the design in this research is Pretest-Posttest Control Group Design. The research population was all fourth grade students at SD Negeri 3 Sigli by taking two classes as samples and using the Total Sampling technique. Data collection was carried out using tests in the form of Pretest-Posttest, while the data analysis technique used SPSS Statistics 29 and hypothesis testing using the Independent t-test. The results of hypothesis testing with independent t-test statistics obtained a significant value (2-tailed) of 0.001 0.05. So the decision making criteria, namely Ha, is accepted, H0 is rejected. Thus it can be concluded that there is a significant influence in the use of ICT (Information and Communication Technology) on student learning outcomes in class IV fraction material at SD Negeri 3 Sigli